ANALYSIS OF PERFORMANCE AND STRATEGIES FOR FINANCIAL MANAGEMENT IN THE CITY OF BOGOR FROM 2014 TO 2023 - Agianto, Kus (Qawwam : The Leader's Writing, 2025)
This study aims to analyze the financial performance of the Bogor City Regional Government during the period 2014 2023 and to develop projections for 2024 2029. Using descriptive analysis and financial ratio methods, this study evaluates aspects of revenue, expenditure, and budget balance. The results of the analysis show dynamics in Local Own-Source Revenue (PAD) and capital expenditure efficiency, which form the basis for policy recommendations for long-term fiscal stability.